Deqi Sensations of Transcutaneous Electrical Nerve Stimulation on Auricular Points. (9th July 2013) - Wang, Xiaoling; Fang, Jiliang; Zhao, Qing; Fan, Yangyang; Liu, Jun; Hong, Yang; Wang, Honghong; Ma, Yunyao; Xu, Chunhua; Shi, Shan; Kong, Jian; Rong, Peijing
Abstract : Deqi sensation, a psychophysical response characterized by a spectrum of different needling sensations, is essential for Chinese acupuncture clinical efficacy. Previous research works have investigated the component of Deqi response upon acupuncture on acupoints on the trunk and limbs. However, the characteristics of Deqi sensations of transcutaneous electrical nerve stimulation (TENS) on auricular points are seldom reported. In this study, we investigated the individual components of Deqi during TENS on auricular concha area and the superior scapha using quantitative measurements in the healthy subjects and depression patients. The most striking characteristics of Deqi sensations upon TENS on auricular points were tingling, numbness, and fullness. The frequencies of pressure, warmness, heaviness, and soreness were relatively lower. The dull pain and coolness are rare. The characteristics of Deqi were similar for the TENS on concha and on the superior scapha.